Analisis Penggunaan Smartphone Wisatawan Muslim Gen-Z: Sebuah Penelitian Interpretative Phenomenology Analysis - Kurnia, Agus; Sugiyanto, Catur; Purnomo, Boyke Rudy; Kusworo, Hendrie Adji (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
Halal tourism is becoming increasingly popular among Muslim tourists interested in international travel. Internationally, Muslim tourists who travel a lot are young tourists, on average 24 years old, and have a good education. Statistically, Generation Z dominates travel in Indonesia. Generation Z is a generation born between 1993-2012 (30-11 years old) and known as "digital natives," which means they quickly adapt to digital technologies and are always connected to the internet and social networks. Understanding the behavior of Generation Z has never been separated from using smartphones. So, understanding the behavior of generation Z travelers in using smartphones on the go is important because they are a potential market in the development of the halal tourism industry in the next 10-15 years. This study focuses on understanding the influence of smartphone digital technology on the behavior of generation Z Muslim tourists in Indonesia when traveling in tourist destinations. This study uses an interpretive phenomenological analysis methodology by conducting in-depth interviews and observations of Gen-Z Muslim travelers using smartphones. The data obtained is then processed using NVIVO software. Data analysis used six stages of interpretive phenomenological analysis. The results in the study will show the superordinate theme that arises from the process of interpreting the experiences of the participants with evidence as presented by the participants.